Estilos de aprendizaje y rendimiento académico en matemática en los alumnos del VII ciclo de una institución educativa del Callao - Borja Torres, Rolando Juan (2010)
This research aims to find the relationship between learning styles and the academic performance in the area of mathematics of students in the seventh cycle of an educational institution of Callao. The instrument used to measure the learning styles was the questionnaire CHAEA and the evaluation records were taken for the academic performance. Taking the data collected, we used the SPSS data processor to look for a correlation, concluding that there is a positive relationship only between the reflective style and academic achievement in the area of mathematics.